File encryption by iris recognition system - Musab A. M. Ali,; Nooritawati Md Tahir,; Al-Rawe, Israa (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper designs a framework for an iris recognition system to obtain significant information by encryption and decryption using iris recognition system to improve the security level of stored extended data. Iris feature to confirm the character of an individual person to grant access to the information document. The strategy is extracted using 1D filter Log-Gabor which has high decidability and minimum variance between (inter & intra) class. In this paper, the 1D filter Log-Gabor was applied, the results are based on FAR and FRR, as feature selection models with SVM type nonlinear quadratic as classifiers CASIA datasets were used. The iris image captured by a high-resolution webcam is used to enter a record that identifies the eligible individual as the beneficiary. The prepared image is matched with the registered iris in the dataset and only if a match is found, it is included in the file. It adds to the assortment of information by providing evidence of the usefulness of the iris in verifying the person, it shows that the iris is very reliable. Segmentation specific area only clarifies the exhibit of this exploration work novel strategy among iris segmentation procedures, all together in restricting the pupil before limiting the iris.